Staff education, regular sedation and analgesia quality feedback, and a sedation monitoring technology for improving sedation and analgesia quality for critically ill, mechanically ventilated patients: a cluster randomised trial. Issue 10 (October 2016) - Walsh, Timothy S; Kydonaki, Kalliopi; Antonelli, Jean; Stephen, Jacqueline; Lee, Robert J; Everingham, Kirsty; Hanley, Janet; Phillips, Emma C; Uutela, Kimmo; Peltola, Petra; Cole, Stephen; Quasim, Tara; et al.
Summary: Background: Optimal sedation of patients in intensive care units (ICUs) requires the avoidance of pain, agitation, and unnecessary deep sedation, but these outcomes are challenging to achieve. Excessive sedation can prolong ICU stay, whereas light sedation can increase pain and frightening memories, which are commonly recalled by ICU survivors. We aimed to assess the effectiveness of three interventions to improve sedation and analgesia quality: an online education programme; regular feedback of sedation–analgesia quality data; and use of a novel sedation-monitoring technology (the Responsiveness Index [RI]). Methods: We did a cluster randomised trial in eight ICUs, which were randomly allocated to receive education alone (two ICUs), education plus sedation–analgesia quality feedback (two ICUs), education plus RI monitoring technology (two ICUs), or all three interventions (two ICUs). Randomisation was done with computer-generated random permuted blocks, stratified according to recruitment start date. A 45 week baseline period was followed by a 45 week intervention period, separated by an 8 week implementation period in which the interventions were introduced. ICU and research staff were not masked to study group assignment during the intervention period. All mechanically ventilated patients were potentially eligible. We assessed patients' sedation–analgesia quality for each 12 h period of nursing care, and sedation-related adverse events daily. Our primary outcome was the proportion of care periods with optimal sedation–analgesia, defined as being free from excessive sedation, agitation, poor limb relaxation, and poor ventilator synchronisation. Analysis used multilevel generalised linear mixed modelling to explore intervention effects in a single model taking clustering and patient-level factors into account. A concurrent mixed-methods process evaluation was undertaken to help understand the trial findings. The trial is registered withClinicalTrials.gov, numberNCT01634451 . Findings: Between June 1, 2012, and Dec 31, 2014, we included 881 patients (9187 care periods) during the baseline period and 591 patients (6947 care periods) during the intervention period. During the baseline period, optimal sedation–analgesia was present for 5150 (56%) care periods. We found a significant improvement in optimal sedation–analgesia with RI monitoring (odds ratio [OR] 1·44 [95% CI 1·07–1·95]; p=0·017), which was mainly due to increased periods free from excessive sedation (OR 1·59 [1·09–2·31]) and poor ventilator synchronisation (OR 1·55 [1·05–2·30]). However, more patients experienced sedation-related adverse events (OR 1·91 [1·02–3·58]). We found no improvement in overall optimal sedation–analgesia with education (OR 1·13 [95% CI 0·86–1·48]), but fewer patients experienced sedation-related adverse events (OR 0·56 [0·32–0·99]). The sedation–analgesia quality data feedback did not improve quality (OR 0·74 [95% CI 0·54–1·00]) or sedation-related adverse events (OR 1·15 [0·61–2·15]). The process evaluation suggested many clinicians found the RI monitoring useful, but it was often not used for decision making as intended. Education was valued and considered useful by staff. By contrast, sedation–analgesia quality feedback was poorly understood and thought to lack relevance to bedside nursing practice. Interpretation: Combination of RI monitoring and online education has the potential to improve sedation–analgesia quality and patient safety in mechanically ventilated ICU patients. The RI monitoring seemed to improve sedation–analgesia quality, but inconsistent adoption by bedside nurses limited its impact. The online education programme resulted in a clinically relevant improvement in patient safety and was valued by nurses, but any changes to behaviours did not seem to alter other measures of sedation–analgesia quality. Providing sedation–analgesia quality feedback to ICUs did not appear to improve any quality metrics, probably because staff did not think it relevant to bedside practice. Funding: Chief Scientist Office, Scotland; GE Healthcare.